Open-Label Uncontrolled, Monocentric Study to Evaluate the Efficacy and Safety of the Electromagnetic Field and Negative Pressure in the Treatment of Cellulite - Antonio Scarano; Antonio Calopresti; Salvatore Marafioti; Gianluca Nicolai; Erda Qorri (Life)
Cellulite is a widespread aesthetical dermatological condition affecting a significant proportion of postpubertal women, characterized by dimpled skin, primarily on the thighs, buttocks, and hips, which has an important psychological impact. Cellulite, also called lipodystrophy or oedematosclerotic panniculitis, causes an aesthetic change in the skin that affects the epidermis, dermis, hypodermis and subcutaneous fat in different ways. The aim of the present prospective study research was to evaluate the efficacy of electromagnetic field and negative pressure in the treatment of cellulite. Methods: A total of 35 women with an average age of 40, ranging from 18 to 50 (mean 32.2 ± 7.48), with a body mass index between 18.5 and 26.9 (mean 22 ± 3.01), were enrolled in this study. The degree of cellulite of the patients was assessed clinically using the Cellulite Severity Scale (CSS) and Nürnberger–Müller classification. All patients received one session per week for a total 12 treatment sessions with Bi-one® LifeTouchTherapy medical device (Expo Italia Srl—Florence—Italy), which generates a combination of vacuum and electromagnetic fields (V-EMF). Total treatment time was approximately 20–30 min per patient. The GAIS score, Cellulite Severity Scale (CSS) and Nürnberger–Müller classification for cellulite was evaluated 1 month after the 12 treatments with LifeTouchTherapy. Results: A statistical difference was recorded in cellulite improvement by visual analog scale (VAS) and global aesthetic improvement scale (GAIS). Conclusions: The results of the present prospective clinical study show the efficacy and safety of Bi-one® LifeTouchTherapy in the treatment of cellulite. Electromagnetic fields combined with negative pressure therapy promote tissue regeneration and reduce fibrosis, which results in visible cosmetic improvements of cellulite.